„Tworki” Marka Bieńczyka jako powieść gatunkowa - Marecki, Piotr (Przestrzenie Teorii, 2012)
The article’s author analyses Marek Bieńczyk’s novel Tworki (1999), using tools from genre theory and challenging the prevailing view of Bieńczyk as a postmodernist, the pantextualism of his literature, and his adherence to “non-epic prose.” Bieńczyk’s novel is contextualized as a drawnout story (gawęda), mystery story, bildundsroman. It is shown how Bieńczyk uses established genres to assemble the elements of a narrative universe (the narrator, protagonist, intrigue), and the way he handles the epic aspects of his literature. Particular emphasis is placed on an analysis of the vaudeville-cabaret layers of the novel, everything borrowed from popular culture and used to re-narrate the trauma of the Holocaust. In this respect, Bieńczyk’s novel is considered to be one of the bravest works in Polish post-1989 literature.